A new stratigraphic inshight of the Upper Pliocene-Lower Pleistocene succession of Lower Valdarno (Tuscany Italy) - SARTI, GIOVANNI; ZANCHETTA, GIOVANNI; Testa G. (2008)
The post-Middle Pliocene stratigraphic evolution of lower Valdarno (northern Tuscany) is reviewed at the light of new stratigraphic data and facies analysis, integrated with the detailed geological mapping of a key area located north and south of the lower course of Arno River, between the towns of Pontedera and S. Croce sull'Arno. The results are discussed taking into account the evolution of extensional tectonics. Three new al- lostratigraphic units (AU) are recognized in the Upper Pliocene-Lower Pleistocene successions on both sides of Lower Valdarno. The stratigraphic position of the widest marine ingression is considered a key element for correlation. The correlation proposed shows an increase in thickness northeastwards, which is here interpreted as due to deposition in a syn-rift half-graben setting. After a generalized uplift during Middle-Late Pliocene, renewed sedimentation occurred in the northeastern sector of the studied area, with partial communication with the sea and development of a lower delta-plain succession. After this first Late Pliocene phase, a new cycle followed on the whole studied area, with documented connection to the sea only in the northeastern sector. Successively, another cycle developed on both sides and deposition of open-marine Artica islandica-bearing deposits occurred. The last cycle (Early Pleistocene), constituted by transitional to continental deposits, is documented in the southern sector only.